Assessment of Unusual Gigantic Jets observed during the Monsoon season: First observations from Indian Subcontinent. Issue 1 (December 2017) - Singh, Rajesh; Maurya, Ajeet; Chanrion, Olivier; Neubert, Torsten; Cummer, Steven; Mlynarczyk, Janusz; Cohen, Morris; Siingh, Devendraa; Kumar, Sushil
Abstract Gigantic Jets are electric discharges from thunderstorm cloud tops to the bottom of ionosphere at 90 km altitude and electrically connect the troposphere and lower ionosphere. Since their first report in 2002, sporadic observations have been reported from ground and space based observations. Here we report first observations of Gigantic Jets in Indian subcontinent over the Indo-Gangetic plains during the monsoon season. Two storms each produced two jets with characteristics not documented so far. Jets propagated 37 km up remarkably in 5 ms with velocity of 7.4 × 106 ms−1 and disappeared within 40–80 ms, which is faster compared to jets reported earlier. The electromagnetic signatures show that they are of negative polarity, transporting net negative charge of 17–23 C to the lower ionosphere. One jet had an unusual form observed for the first time, which emerged from the leading edge of a slowly drifting complex convective cloud close to the highest regions at 17 km altitude. A horizontal displacement of 10 km developed at 50 km altitude before connecting to the lower ionosphere. Modeling of these Gigantic jets suggests that Gigantic Jets may bend when initiated at the edge of clouds with misaligned vertical charge distribution.